(untitled) (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2021)
The focus of this research is to explain the representation of Javanese folklore in the methik and gejug lesung traditions at Glinggang Village, Sampung District, Ponorogo Regency. The purpose of this study is to describe the representation of folklore in the tradition. The method used in this study is a descriptive qualitative. Data collection techniques used are interviews and observation. The results showed that the people in Glinggang Village still held the methik and gejug lesung traditions as a form of gratitude to God. In addition, these traditions are also intended to increase the value of mutual cooperation, strengthen ties of friendship, maintain food stability, and improve the economy of local residents.